Pengembangan Model Pembelajaran Kontekstual Berbasis Etnomatematika Tradisi Weaving Bima untuk Meningkatkan Identitas Budaya dan Pemahaman Simetri - Rizcky Juliawan; Muhammad Salahuddin (Faculty of Mathematics and Natural Sciences, Universitas Negeri Surabaya, 2026)
Mathematics education in schools still faces various problems, especially on abstract materials such as geometry and symmetry. Students often experience difficulties in understanding concepts because learning is still conventional, lacks media, and rarely connects the material with students' life experiences. In addition, the utilization of local Bima culture in mathematics learning has not been optimal, although the Bima weaving tradition has many elements that can be used as learning contexts, including woven motifs that are rich in geometry and repeating patterns. This study aims to develop a contextual learning model based on the ethnomathematics of the Bima weaving tradition that is valid, practical, and effective to enhance students' cultural identity and understanding of symmetry. This study uses an Educational Design Research (EDR) approach with the McKenney and Reeves model, which includes three stages: analysis and exploration, design and construction, and evaluation and reflection. The research subjects consisted of material experts, learning experts, Bima cultural experts, mathematics teachers, and grade VIII students of SMPN 3 Woha. Research data were obtained through observations, interviews, questionnaires, symmetry comprehension tests, and documentation. The results showed that the developed learning model met the criteria of valid with an average validity score of 91.2% (very valid), practical with an average practicality score of 91.5% (very practical), and effective with an N-Gain value of 0.59 (moderate to high category). Furthermore, this model is also effective in enhancing students' cultural identity from a score of 68% before learning to 86% after learning. The final product of this study is a contextual learning model based on the ethnomathematics of the Bima weaving tradition, equipped with learning syntax, teaching devices, LKPD, evaluation instruments, and implementation guidelines for teachers.